Pengaruh E-Modul Terhadap Kepatuhan Orang Tua Dalam Melaksanakan Prosedur Pencegahan Infeksi Luka Pasca Palatoplasty Di RSGM Unpad - Warsito, Aliffiani; Sodja Laela, Dewi; Fatikhah, Nurul; Marah Laut, Deru (Jurnal Terapi Gigi dan Mulut, 2024)
Wound infection after palatoplasty surgery often occurs due to lack of understanding and compliance of parents in performing wound care after palatoplasty surgery. Wound infection prevention procedures must be carried out in accordance with the instructions given by health workers, in order to avoid the occurrence of infection. Compliance of parents can be improved by giving instructions using media, electronic modules are used as one of the media aids that can be used. The purpose of this study was to see the effect of using electronic modules on the level of parental compliance in implementing wound infection prevention procedures after palatoplasty surgery at RSGM UNPAD. This study is a quasi-experiment study, with a Posttest Only Control Group Design research design, the level of parental compliance is measured using a questionnaire of compliance with the prevention of wound infection after palatoplasty surgery. Samples were taken using accidental sampling technique, which is taking samples that meet the criteria. Analysis through the Mann-Whitney U test showed a significant effect with a value (p-value 0.005 <0.05) on the level of compliance of parents of patients who were given electronic modules regarding the prevention of wound infections after palatoplasty surgery. The use of electronic modules affects parental compliance in carrying out procedures for preventing wound infection after palatoplasty surgery. It is hoped that this e-module can be utilized to present information interactively, so that parents are more compliant to follow the recommended procedures.